(3ehGRfI Hjf efgLj eOQSI GdefGQ heOQSI GdCefGA aj JaSjQ hYdhe GdbQBf (B/s - (3GdZQjH, QeVGf NejSs; (3YeGQI, eMeOs 1931-2020 ([(3O(B.(3e(B]s (3OGQ GdHTjQ ddKbGaI hGdYdhes, 2018)
(3gPG GdcJGH OQGSI YdejI LGeYjI, fGd HgG UGMHgG OQLI GdOcJhQGg aj GdJaSjQ hYdhe GdbQBf, HeQJHI GdTQa GdChdi ef LGeYI GdCRgQ, hgj JLdj dfG MdbI eabhOI ef efgLj eOQSI GdefGQ heOQSI GdCefGA aj GdJaSjQ hYdhe GdbQBf hdCf JCKjQ gGJjf GdeOQSJjf(B- (3aj GdJaSjQ(B- (3dG jRGd egjefG Ydi JjGQGJ acQfG GdeYGUQ, JCKjQ GdeOQSI GdEUdGMjI aj GdeMjW GdESdGej hJCKjQ GdeOQSI GdHjGfjI aj bWGY ef GdeMjW GdYdeGfj hGdMOGKj, cGfJ gPg GdOQGSI SHGMI eGgQI aj JjGQGJ GdacQ, hefGgL GdEUdGM, hNjGQGJ GdJbOe GdJj fJfaSgG aj hGbYfG GdacQj GdeYjT(B.s
(3HHdjhLQGajI (B: (3UaMI (B428-439.s
Keywords: (3JaSjQ GdbQBf GdcQjes -- (3efGgL Yde GdJaSjQs